Analisa Penggunaan Turbin Angin Hibah China HD1000 dengan Turbin Angin Sejenisnya Kapasaitas 1 MW/Unit untuk Daerah Pulau Sabang, Provinsi Aceh - Benny Susanto; Rasgianti Rasgianti (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
The purpose of this study is to find out in general the condition of the AVIC wind turbines that will be donated when compared to similar wind turbines that have been proven. This study is still early and early in nature because it was only carried out by a desk study with reference to AVIC Wind Turbine technical data originating from the Central PLN without conducting field tests and surveys. This study is limited only from a mechanical point of view, namely a comparison of the Power Curve, Capacity Factor and energy production of the AVIC Wind Turbine with similar wind turbines that are already on the market using the Homer software. The simulation was carried out by comparing the AVIC Huide HD1000 wind turbine with a capacity of 1MW with wind turbines with typical capacities on the application HOMER, namely Leitwind 77, Leitwind 80, Leitwind 86 and Leitwind 90. The selected location is the location being studied by the PLN Puslitbang because load data is already available namely Sabang Island